All Days 1994
DOI: 10.4043/7620-ms
|View full text |Cite
|
Sign up to set email alerts
|

Design And Installation Of Auger Steel Catenary Risers

Abstract: The Auger export pipelines are connected to the TLP by steel catenary risers (SCRs). This is believed to be theftrst time steel pipe has been used for catenary risers. SCRs offer advantages over tensioned risers, since SCRs need no heave compensation and no subsea connections, and over risers made of "flexible pipe", since SCRs are much less expensive. However, significant design effort was required to prove that the SCRs could safely withstand environmental loads and the effects of TLP motions. The design eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Figure 5 shows the cross-section of the riser under investigation, where the inner layer of 3 mm is duplex stainless steel, and the rest of 14 mm is carbon manganese steel. The sizing of the riser is as per the existing riser of Auger TLP [17] . X-ray computed Tomography test on the FGM build confirmed that it is free from porosity and micro-cracks.…”
Section: Functionally Graded Materialsmentioning
confidence: 99%
“…Figure 5 shows the cross-section of the riser under investigation, where the inner layer of 3 mm is duplex stainless steel, and the rest of 14 mm is carbon manganese steel. The sizing of the riser is as per the existing riser of Auger TLP [17] . X-ray computed Tomography test on the FGM build confirmed that it is free from porosity and micro-cracks.…”
Section: Functionally Graded Materialsmentioning
confidence: 99%
“…6), and Lazy Wave configurations in steel and titanium have been proposed as deep-water riser systems for TLP and Semisubmersibles. Free Hanging Risers in steel have been installed in the Gulf of Mexico (Ref.…”
Section: Deep Water Systemsmentioning
confidence: 99%
“…The SCR configuration forms catenary due to its own weight. The SCR also offers benefit over the top tensioned riser because the SCR requires no heave compensation at the hang-off point (Phifer et al, 1994). On the seabed, the SCR needs no special bottom connection.…”
Section: Introductionmentioning
confidence: 99%
“…The steel catenary riser (SCR) has emerged to be one of attractive choices for recent deep water environments (Phifer et al, 1994). The steel catenary riser consists of simple rigid steel pipe hanging freely from the floating production system to the seabed.…”
Section: Introductionmentioning
confidence: 99%